Relasi Politik Islam Terkait Islam Aceh dan Islam Turki - Kurdi, Sulaiman; Alamudi, Ichwan Ahnaz (Matan : Journal of Islam and Muslim Society, 2023)
This article seeks to explain Islamic thought related to the relationship between Acehnese Islam and Turkish Islam both through political and religious sectors that the author adopted as more dominant. The relationship between the two was harmonious even though it was said that Aceh and Turkey had such a long distance, so the argument about the harmonious relationship was so evocative of the treasure of thought to be followed up. This study aims to find out how the history of Thought relates to the Islamic Relations of Aceh and Turkey in Islamic politics. The method used in the study is a literature review (library research). So in this study the authors found that in the political field when the Kingdom of Aceh was in the Dutch colonial hegemony barrier, the kingdom of Turkey helped Aceh both from helping logistics related to military weaponry and even participated in sending troops to Aceh. Then, on the other side of the relationship with religion, the author found related to the jihad of the Acehnese people as a spirited and very tempestuous spirit naya in the Aceh war which is often told through the saga of the sabil war.